Artificial Skin Perception. Issue 19 (15th September 2020) - Wang, Ming; Luo, Yifei; Wang, Ting; Wan, Changjin; Pan, Liang; Pan, Shaowu; He, Ke; Neo, Aden; Chen, Xiaodong
Abstract: Skin is the largest organ, with the functionalities of protection, regulation, and sensation. The emulation of human skin via flexible and stretchable electronics gives rise to electronic skin (e‐skin), which has realized artificial sensation and other functions that cannot be achieved by conventional electronics. To date, tremendous progress has been made in data acquisition and transmission for e‐skin systems, while the implementation of perception within systems, that is, sensory data processing, is still in its infancy. Integrating the perception functionality into a flexible and stretchable sensing system, namely artificial skin perception, is critical to endow current e‐skin systems with higher intelligence. Here, recent progress in the design and fabrication of artificial skin perception devices and systems is summarized, and challenges and prospects are discussed. The strategies for implementing artificial skin perception utilize either conventional silicon‐based circuits or novel flexible computing devices such as memristive devices and synaptic transistors, which enable artificial skin to surpass human skin, with a distributed, low‐latency, and energy‐efficient information‐processing ability. In future, artificial skin perception would be a new enabling technology to construct next‐generation intelligent electronic devices and systems for advanced applications, such as robotic surgery, rehabilitation, and prosthetics. Abstract : Artificial skin perception that integrates the perception functionality into a flexible and stretchable sensing system could endow current flexible electronic devices with higher intelligence. The recent progress, challenges, and prospects of artificial skin perception are discussed, offering some inspiration for the development of next‐generation intelligent systems, especially soft robotics.